Wind energy in Bangladesh: recent developments, challenges and policy recommendations - M., Shahabuddin; Md Rezaur, Rahman; N.W. M., Zulkifli; Mayeen Uddin, Khandaker; Y. Y., Liang (Springer Nature, 2025)
Bangladesh is actively diversifying its energy mix, with wind power emerging as a promising yet underutilised resource. This review evaluates the current status, challenges, and prospects of wind energy in Bangladesh, supported by comparative insights from regional leaders such as India, Vietnam, and Pakistan. Despite a theoretical potential of at least 30 GW, Bangladesh has only grid connected installed capacity of 63 MW, contributing marginally to its 28,132 MW total generation, of which total renewables account for just 3.54%. The government has set an over ambitious target of 5.0 GW of wind by 2030, with some notable projects in the coastal areas. Based on the current review there is a favourable wind conditions along the southern coastal belt, where average wind speeds range 5.5–7.2 m/s at 100 m hub heights, rising above 7.0 m/s during the monsoon (May–July). However, development is constrained by inadequate inland wind velocities, limited high-resolution data, high capital expenditures (USD 1900–2100/kW), fragile grid infrastructure, cyclone exposure, and regulatory bottlenecks. Key recommendations include expanding offshore and floating wind projects, adopting wind-solar hybrid systems with smart grids and storage, strengthening domestic R&D capacity, and implementing dedicated wind energy policies with bankable incentives such as auctions, FiTs, and green bonds. Enhancing community acceptance through participatory planning and mitigating ecological risks will also be critical. Comparative case studies show that with clear policies and investment frameworks, countries with similar constraints have achieved rapid capacity expansion. For Bangladesh, aligning policy, finance and technology with global best practices can transform wind energy into a strategic pillar of its 2041 vision of sourcing 40% of electricity from renewables.